ORGANIZATIONAL AGILITY AND ITS ROLE IN REDUCING JOB INERTIA FOR MANAGERS OF SPORTS TALENT DEPARTMENTS FROM THE PERSPECTIVE OF SPORTS SUPERVISORS - Mustafa Talib Hammadi; Assist. prof. Dr. Ibrahim Faisal Khalaf (Proximus Journal Publishing, 2024)
The following goals were the main goals of the study: 1. Building scales (job inertia and organizational agility) for managers of sports talent departments from the viewpoint of sports supervisors. 2. From the standpoint of sports supervisors, determining the organizational agility and work inertia levels of managers of sports talent departments. Using survey and correlational methods, the researcher used a descriptive methodology. The study population comprised sports supervisors from fifteen departments, totaling 185 sports supervisors, which were linked with the Ministry of Youth and Sports in Iraq. The data were analyzed using a complete census method, and the data processing was done using the statistical package SPSS 26. The researcher came to several results, the most significant of which are as follows: 1. Sports talent departments have access to organizational agility dimensions, showing that the sample under study is aware of and perceives this variable. 2. Based on their individual capabilities in various aspects of their work within those departments, the results showed shortcomings in the management of sports talent departments in terms of comprehending and assessing the strengths and weaknesses of employees as well as the lack of clear standards for keeping an eye on and holding them accountable
Keywords: Organizational agility; job inertia